2021
DOI: 10.1186/s12935-021-02304-0
|View full text |Cite
|
Sign up to set email alerts
|

YTHDC1-mediated VPS25 regulates cell cycle by targeting JAK-STAT signaling in human glioma cells

Abstract: Background Glioma is a common type of malignant brain tumor with a high mortality and relapse rate. The endosomal sorting complex required for transport (ESCRT) has been reported to be involved in tumorigenesis. However, the molecular mechanisms have not been clarified. Methods Bioinformatics was used to screen the ESCRT subunits highly expressed in glioma tissues from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…Meanwhile, VPS25 induced a G0/G1 phase arrest of the cell cycle in glioma cells by directly mediating p21, CDK2, and cyclin E expression, and JAK-signal transducer and activator of transcription (STAT) activation. These results suggest that VPS25 is a promising prognostic indicator and a potential therapeutic target for glioma (Zhu et al, 2021).…”
Section: Janus Kinase/signal Transducer and Activator Of Transcriptio...mentioning
confidence: 69%
See 1 more Smart Citation
“…Meanwhile, VPS25 induced a G0/G1 phase arrest of the cell cycle in glioma cells by directly mediating p21, CDK2, and cyclin E expression, and JAK-signal transducer and activator of transcription (STAT) activation. These results suggest that VPS25 is a promising prognostic indicator and a potential therapeutic target for glioma (Zhu et al, 2021).…”
Section: Janus Kinase/signal Transducer and Activator Of Transcriptio...mentioning
confidence: 69%
“…Signaling cross-talk between JAK/STAT and other pathways is an intricate and colossal network, happens at different levels, and covers varieties of molecules, such as a ligand, receptor, phosphorylation, JAK, STAT, and gene transcription factors etc. (Zhu et al, 2021). These cross-talk activities play crucial roles in pluripotency and differentiation transcription program, immune regulation, and tumorigenesis.…”
Section: Signaling Cross-talk Between Janus Kinase/signal Transducer ...mentioning
confidence: 99%
“…YTHDC1 modulates MCM complex-mediated DNA replication and promotes leukemogenesis [ 16 ]. However, YTHDC1 was reported to suppress the progression of glioma by inhibiting VPS25 [ 41 ]. Moreover, YTHDC1 was also found to inhibit glycolysis in pancreatic cancer through the miR-30d/RUNX1 axis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al. demonstrated that YTHDC1 inhibits glioma cells proliferation by decreasing VPS25 expression ( 141 ). Liu et al.…”
Section: M6a Modification and Glioblastomamentioning
confidence: 99%